2013
DOI: 10.3168/jds.2012-6497
|View full text |Cite
|
Sign up to set email alerts
|

Protein, casein, and micellar salts in milk: Current content and historical perspectives

Abstract: The protein and fat content of Dutch bulk milk has been monitored since the 1950s and has increased considerably, by 11 and 20%, respectively, whereas milk yield has more than doubled. The change in protein and fat content of milk is advantageous for the dairy industry, as these are the 2 most economically valuable constituents of milk. Increases in protein and fat content of milk have allowed increases in the yield of various products such as cheese and butter. However, for cheese and other applications where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
70
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 35 publications
(46 reference statements)
16
70
0
2
Order By: Relevance
“…Milk is the main source of Ca in human diet (Haug et al, 2007;Bonjour et al, 2009;Zamberlin et al, 2012). Also, Ca, P and Mg are partially bonded to the casein micelles (Gaucheron, 2005;Zamberlin et al, 2012), influencing mi-celle structure and stability, and thus milk coagulation and curd rheology (Bijl et al, 2013;Malacarne et al, 2014;Petrera et al, 2016;Lucey et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Milk is the main source of Ca in human diet (Haug et al, 2007;Bonjour et al, 2009;Zamberlin et al, 2012). Also, Ca, P and Mg are partially bonded to the casein micelles (Gaucheron, 2005;Zamberlin et al, 2012), influencing mi-celle structure and stability, and thus milk coagulation and curd rheology (Bijl et al, 2013;Malacarne et al, 2014;Petrera et al, 2016;Lucey et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Ca, P and Mg are partially bonded to the casein micelles (Gaucheron, 2005;Zamberlin et al, 2012), influencing mi-celle structure and stability, and thus milk coagulation and curd rheology (Bijl et al, 2013;Malacarne et al, 2014;Petrera et al, 2016;Lucey et al, 2017). Concentrations of Ca, P and Mg in milk are negatively correlated with rennet coagulation time (RCT, min) and curd-firming time (k 20 , min), and positively correlated with curd firmness 30 min after rennet addition (a 30 , mm) and titratable acidity (Toffanin et al, 2015;Visentin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Substantial differences among cattle breeds for milk composition, rennet coagulation properties (RCP), mineral content and cheese quality have been observed (Malacarne et al 2006;De Marchi et al 2007;van Hulzen et al 2009) and attributed to genetic factors The colloidal fractions of calcium (Ca), phosphorus (P) and magnesium (Mg) are essential constituents of the micelles, influencing their structure and functionality, with repercussion on milk rennetability and cheese texture (Gaucheron 2005;Bijl et al 2013;Malacarne et al 2014). Moreover, minerals are of major importance when considering the nutritional value of milk (Piril€ a et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that good and poor coagulating milks generally present either the same level of CN content (Hallén et al 2010;Frederiksen et al 2011b;Bijl et al 2014) or a lower CN level in the poorly coagulating (Jensen et al 2012;Malacarne et al 2014), depending on study, method of assessment of coagulation class, and number of samples. However, in poorly coagulating milk, a lower amount of Ca might not had been enough to neutralize the negatively charged phosphorylated regions of the Casensitive casein fractions (α S1 -, α S2 -and β-CN) and minimize inter-molecular repulsion (Frederiksen et al 2011a;Bijl et al 2013). Therefore, the prevalence of negative charges in micelles with lower amount of both micellar and total Ca could have prevented the second aggregation phase of rennet-induced coagulation as suggested by Jensen et al (2012).…”
Section: Discussionmentioning
confidence: 99%